2021
DOI: 10.3390/pr9020388
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Carbon Quantum Dots: Properties, Fabrication Techniques, and Bio-Applications

Abstract: Carbon dots have gained tremendous interest attributable to their unique features. Two approaches are involved in the fabrication of quantum dots (Top-down and Bottom-up). Most of the synthesis methods are usually multistep, required harsh conditions, and costly carbon sources that may have a toxic effect, therefore green synthesis is more preferable. Herein, the current review presents the green synthesis of carbon quantum dots (CQDs) and graphene quantum dots (GQDs) that having a wide range of potential appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 170 publications
1
45
0
Order By: Relevance
“…Although using excellent properties such as low toxicity [140] and good biocompatibility makes CQDs ideal materials for bioimaging, biosensors and drug delivery applications, CQDs can, however, offer advantages in catalysis, sensors and optronics based on their excellent optical and electronic properties [123].…”
Section: Emerging Applications Of Carbon Dotsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although using excellent properties such as low toxicity [140] and good biocompatibility makes CQDs ideal materials for bioimaging, biosensors and drug delivery applications, CQDs can, however, offer advantages in catalysis, sensors and optronics based on their excellent optical and electronic properties [123].…”
Section: Emerging Applications Of Carbon Dotsmentioning
confidence: 99%
“…Das et al, reported the use of carbon dots in the field of medicine and bio imaging [123]. Shabasy et al, also reported the detailed applications of C-dots in the biological field including bio imaging [140]. Several studies were carried out where CDs have been used for bioimaging; these are briefed in Table 10.…”
Section: Bioimagingmentioning
confidence: 99%
See 3 more Smart Citations